Emission-Assisted Maintenance for Advanced Diesel Engines and Exhaust Aftertreatment Systems in Underground Mining - Bugarski, Aleksandar D (Mining, metallurgy & exploration, 2025)
Maintaining the particulate emissions from contemporary diesel engines equipped with diesel particulate filter (DPF) systems at targeted levels and assuring the effectiveness of DPF systems retrofitted to traditional diesel engines are critical to the efforts of underground mining operations to reduce exposures of miners to diesel particulate matter. The methodologies and instrumentation currently used to support the emission-assisted maintenance (EAM) programs for previous generations of diesel engines are in need of improvement to allow for monitoring low concentrations of complex aerosols emitted by the advanced diesel engines. The results showed that of the test conditions currently used in EAM programs, the torque converter stall and hydraulic stall are the most suitable for assessing the effectiveness of the DPF-based advanced aftertreatment systems. The low idle and high idle test conditions, frequently used in EAM programs for traditional engines, did not produce reliable and reproducible data. The solid particle number (SPN) concentrations proved to be more suitable than total particulate number concentrations as a metric for EAM monitoring of diesel aerosols emitted by advanced diesel engines. Both of the evaluated direct reading instruments, TSI 3795-HC and Pegasor Mi3, provided comparably accurate results of assessments of the SPN concentrations in the targeted range of concentrations between 2 × 10 and 3 × 10 #/cm . Those proved to be viable EAM tools for determination of the efficiencies and performance degradation of the DPF system. The findings of this study should provide the underground mining industry with valuable information needed to enhance their EAM programs.